UNDERSTANDING CONFLICT MATERIALS AND CONFLICT RESOLUTION THROUGH PICTURED E-MODULES FOR SENIOR HIGH SCHOOL STUDENTS - Susi Fitria Dewi; Fatmariza Fatmariza; Nosy Mutia Angraini; Susi Karmila (Universitas Negeri Medan, 2021)
There has been an increase in teacher creativity to develop various learning media during the pandemic. This paper has the aim of showing one form of developing high school Civics teaching materials, namely conflict and conflict resolution in the form of a Picture E-Module. There are two problem formulations, namely (1) what is the form of the illustrated E-Modul on Conflict and Conflict Resolution material for high school students? (2) how is the validity of the media and the validity of the illustrated E-Module material? Using the Research and Development (R&D) research method of the Bord and Gall model, the E-Modul trial was conducted on class XII students in four high schools in the city of Padang, with a total of 203 students as respondents. The feasibility of this E-Module in terms of media validity has been tested by two experts with a validity result of 79.1% (Valid). For the validity of the material has been tested by 203 students obtained a validity value of 73.8% (good). The results of the media test and validity test show that this E-Module is quite effective in being used as a learning medium to improve students' understanding of Pancasila and Citizenship Education subjects, especially Conflict and Conflict Resolution materials